Permanent magnetic ferrite-based composite bonded magnet and preparation method thereof
By blending polyphenylene sulfide with modified magnetic powder and preparing permanent magnet ferrite based composite bonding magnets by extrusion injection molding, the problems of low fracture toughness of sintered strontium ferrite permanent magnets and poor magnetic properties of bonding magnets are solved, and the preparation of high-performance magnets is realized.
Patent Information
- Application Number
- CN202411818744.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sintered strontium ferrite permanent magnets have low fracture toughness during the preparation process. When used in permanent magnet motors, the utilization rate of the material is greatly reduced; while the bonded magnets are formed at one time, but the magnetic properties are poor.
Permanent magnet ferrite-based composite bonded magnets are prepared by blending polyphenylene sulfide with modified magnetic powder and extrusion injection molding. The method for preparing modified magnetic powder includes blending tetraethyl orthosilicate and γ-glycidyl etheroxypropyl trimethoxysilane to prepare a modified liquid, modify the surface of the magnetic powder, form a silica coating with epoxy groups, and improve the oxidation resistance and compatibility of the magnetic powder.
It improves the mechanical properties and magnetic properties of bonded magnets, enhances the fluidity and filling ability of the material, realizes the preparation of high-performance magnets, and is suitable for applications such as permanent magnet motors.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of permanent magnetic materials, and in particular to a permanent ferrite-based composite bonded magnet and a preparation method thereof. Background Art
[0002] With the rapid development of electromagnetic and communication technology, electromagnetic waves have received widespread attention in the military and civilian fields. Permanent ferrite is a magnetic ferrite that is not easy to demagnetize after magnetization. It has the characteristics of high saturation magnetization, high remanence and high coercivity. Modern magnetic circuit systems need to generate a stable and unchanging magnetic field, and permanent magnetic materials have important application value in it. In addition, it can also widely replace various magnetic materials and be used in various electroacoustic devices such as speakers and recording heads and instrument control devices. M-type permanent ferrite is widely used in today's industrial production and life because of its relatively low cost. Among the M-type permanent ferrites, barium ferrite and strontium ferrite were studied earlier and more maturely. Among them, strontium ferrite is ferrimagnetic, which determines that its saturation magnetization is not high and is smaller than that of barium ferrite, but it has high coercivity, magnetocrystalline anisotropy, and excellent chemical stability and thermal stability, and has been widely used in the field of high-frequency microwave absorption.
[0003] In order to manufacture high-performance permanent magnet ferrites, the research work mainly focuses on two aspects: crystal structure and microstructure. When a proper amount of substances that can react with each other to generate low melting point substances are added to strontium ferrite, or when low melting point substances are generated with strontium ferrite permanent magnet pre-sintered materials (intermediate phase components, residual impurities, etc.), such as H3BO3, CaCO3 and SiO2, these low melting point substances can produce glass phases during the sintering process, thereby greatly promoting the sintering process, making the sintered magnets more compact, and ultimately improving the magnetic indexes of each phase of strontium ferrite. However, in the subsequent processing results, various defects such as brittle fracture and microcracks are often produced due to its poor mechanical processing performance. Especially when used in permanent magnet motors, fractures and microcracks greatly reduce the utilization rate of materials. Compared with sintered magnets, bonded magnets can be formed in one go, without secondary processing, and can be made into various complex shaped magnets. However, the magnetic properties of bonded magnets are worse than those of sintered magnets. Summary of the invention
[0004] The purpose of the present invention is to provide a permanent ferrite-based composite bonded magnet and a preparation method thereof, so as to solve the following technical problems: The existing sintered strontium ferrite permanent magnet has low fracture toughness during the preparation process, which greatly reduces the material utilization rate when used in permanent magnet motors; while the bonded magnet is formed in one step, but has poor magnetic properties.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a permanent ferrite-based composite bonded magnet comprises the following steps: blending polyphenylene sulfide and modified magnetic powder, and then extruding and injection molding to obtain a permanent ferrite-based composite bonded magnet; The preparation method of modified magnetic powder comprises the following steps: S1: Add tetraethyl orthosilicate and anhydrous ethanol into a reaction kettle and disperse them evenly, add γ-glycidyloxypropyltrimethoxysilane and disperse them evenly, add deionized water, adjust the pH to 4-6, control the temperature to 40-50°C, keep the temperature for reaction for 0.5-1h, and obtain a modified solution; S2: Add magnetic powder and anhydrous ethanol into a reaction kettle and disperse them evenly, add the modified liquid into the reaction kettle, control the temperature at 30-40°C, keep the reaction warm for 3-6 hours, filter and dry to obtain modified magnetic powder.
[0006] As a further solution of the present invention: the addition ratio of tetraethyl orthosilicate, anhydrous ethanol, γ-glycidyloxypropyltrimethoxysilane and deionized water in S1 is 10 mL: 20-40 mL: 1-2 mL: 1-5 mL.
[0007] As a further solution of the present invention: the addition ratio of magnetic powder, anhydrous ethanol and modified liquid in S2 is 10g:20-30mL:3-6mL.
[0008] As a further solution of the present invention: polyphenylene sulfide accounts for 10-12% of the total weight of the bonded magnet.
[0009] As a further solution of the present invention: the temperature of extrusion injection molding is 290-320°C.
[0010] As a further solution of the present invention: the method for preparing magnetic powder comprises the following steps: A1: ball-milling and blending ferric oxide and strontium carbonate, and then pre-calcining to obtain a pre-calcined material; A2: After the pre-sintered material is crushed, magnetic powder is obtained.
[0011] As a further solution of the present invention: the magnetic powder particle size is 1.0-1.8 um.
[0012] As a further solution of the present invention: the molar ratio of ferric oxide to strontium carbonate is 5.5-5.8:1.
[0013] As a further solution of the present invention: the specific procedure of pre-sintering is: heating rate 5-10°C / min, heating to 1100°C-1200°C, keeping warm for 2-4h.
[0014] A permanent ferrite-based composite bonded magnet is made by any one of the above-mentioned preparation methods.
[0015] Beneficial effects of the present invention: (1) The present application uses a modified liquid prepared by mixing tetraethyl orthosilicate and γ-glycidyloxypropyltrimethoxysilane to modify the surface of magnetic powder; tetraethyl orthosilicate and γ-glycidyloxypropyltrimethoxysilane are used to coat the magnetic powder, firstly hydrolyzed to form silanol, and the silanol hydroxyl groups form hydrogen bonds on the surface of the magnetic powder, and further undergo a dehydration reaction to form -Si-OM (M is the surface of the magnetic powder) covalent bonds, and after heating, the silanol molecules of these silane hydrolysis products can also condense and aggregate with each other to form a network structure film covering the surface of the magnetic powder, which is then heated to decompose and form a silicon dioxide coating with epoxy groups on the surface of the magnetic powder; the formation of the coating is achieved by adsorbing on the surface of the magnetic powder through hydroxyl condensation reaction and chemical bonding, effectively improving the oxidation resistance of the magnetic powder.
[0016] (2) In the present application, polyphenylene sulfide is added as a binder, and the epoxy groups of the magnetic powder react with the terminal groups in the polyphenylene sulfide chain segments to enhance the compatibility between the magnetic powder and polyphenylene sulfide, so that the binder is wrapped on the surface of the magnetic powder particles. The silica coating on the surface of the magnetic powder and the epoxy ring opening to connect polyphenylene sulfide not only effectively improve the disadvantage of polyphenylene sulfide's high brittleness, thereby improving the mechanical properties of the bonded magnet; but also improve the fluidity of the material, improve the filling capacity, and improve the orientation of the magnetic powder to obtain a high-performance magnet. During the molding process, a magnetic field can be applied to make anisotropic film pressed magnets.
[0017] (3) This application adopts the traditional solid phase reaction method, with ferric oxide and strontium carbonate as raw materials, after a ball milling mixing, high temperature sintering to generate a premix, the premix is subjected to a second ball milling crushing, effectively promoting the crystal structure to strontium hexagonal ferrite phase transformation, to obtain strontium ferrite magnetic powder; this application controls the magnetic powder particle size to achieve the adjustment of the loose density of the magnetic powder. This application uses the prepared modified magnetic powder and polyphenylene sulfide in combination to prepare bonded magnets, which can make the bonded magnetic composite material achieve a higher magnetic powder filling rate, with the advantages of less binder usage, large proportion of magnetic powder, good density of magnets after molding and good magnetic properties of magnets; and it can effectively improve the impact resistance of the material, and at the same time, with the help of polymer processing methods, various complex shaped products can be obtained, meeting the requirements of near net molding in production. DETAILED DESCRIPTION
[0018] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Embodiment 1 A method for preparing modified magnetic powder comprises the following steps: S1: After ball-milling and blending ferric oxide and strontium carbonate at a molar ratio of 5.8:1, the blended material is sintered in an air atmosphere at a heating rate of 5°C / min to 1150°C and kept at this temperature for 2 hours to obtain a pre-sintered material; the pre-sintered material is crushed to obtain magnetic powder with a particle size of 1.1 um; S2: Add 10 mL of tetraethyl orthosilicate and 20 mL of anhydrous ethanol into the reactor and disperse them evenly, add 1 mL of γ-glycidyloxypropyltrimethoxysilane and disperse them evenly, add 1 mL of deionized water, adjust the pH to 4, control the temperature at 40°C, and keep the reaction for 0.5 h to obtain a modified solution; S3: Add 10 g of magnetic powder and 20 mL of anhydrous ethanol into a reactor and disperse them evenly. Add 3 mL of the modified liquid into the reactor, control the temperature at 30°C, keep the reaction warm for 3 hours, filter and dry to obtain modified magnetic powder.
[0020] Embodiment 2 A method for preparing modified magnetic powder comprises the following steps: S1: After ball-milling and blending ferric oxide and strontium carbonate at a molar ratio of 5.8:1, the blended material is sintered in an air atmosphere at a heating rate of 5°C / min to 1150°C and kept at this temperature for 2 hours to obtain a pre-sintered material; the pre-sintered material is crushed to obtain magnetic powder with a particle size of 1.1 um; S2: Add 10 mL of tetraethyl orthosilicate and 30 mL of anhydrous ethanol into the reactor and disperse them evenly, add 1.8 mL of γ-glycidyloxypropyltrimethoxysilane and disperse them evenly, add 3 mL of deionized water, adjust the pH to 5, control the temperature at 45°C, and keep the reaction for 0.5 h to obtain a modified solution; S3: Add 10 g of magnetic powder and 25 mL of anhydrous ethanol into a reactor and disperse them evenly. Add 5 mL of the modified liquid into the reactor, control the temperature at 35°C, keep the reaction warm for 3 hours, filter and dry to obtain modified magnetic powder.
[0021] Embodiment 3 A method for preparing modified magnetic powder comprises the following steps: S1: After ball-milling and blending ferric oxide and strontium carbonate at a molar ratio of 5.8:1, the blended material is sintered in an air atmosphere at a heating rate of 5°C / min to 1150°C and kept at this temperature for 2 hours to obtain a pre-sintered material; the pre-sintered material is crushed to obtain magnetic powder with a particle size of 1.1 um; S2: Add 10 mL of tetraethyl orthosilicate and 40 mL of anhydrous ethanol into the reactor and disperse them evenly, add 2 mL of γ-glycidyloxypropyltrimethoxysilane and disperse them evenly, add 5 mL of deionized water, adjust the pH to 6, control the temperature at 50°C, and keep the reaction for 1 hour to obtain a modified solution; S3: Add 10 g of magnetic powder and 30 mL of anhydrous ethanol into a reactor and disperse them evenly. Add 6 mL of modified liquid into the reactor, control the temperature at 40°C, keep the reaction warm for 6 hours, filter and dry to obtain modified magnetic powder.
[0022] Embodiment 4 A method for preparing a permanent ferrite-based composite bonded magnet comprises the following steps: 10 g of polyphenylene sulfide and 90 g of the modified magnetic powder prepared in Example 1 were blended and then extruded and injection molded at 310° C. to obtain a permanent ferrite-based composite bonded magnet.
[0023] Embodiment 5 A method for preparing a permanent ferrite-based composite bonded magnet comprises the following steps: 10 g of polyphenylene sulfide and 90 g of the modified magnetic powder prepared in Example 2 were blended and then extruded and injection molded at 310° C. to obtain a permanent ferrite-based composite bonded magnet.
[0024] Example 6 A method for preparing a permanent ferrite-based composite bonded magnet comprises the following steps: 10 g of polyphenylene sulfide and 90 g of the modified magnetic powder prepared in Example 3 were blended and then extruded and injection molded at 310° C. to obtain a permanent ferrite-based composite bonded magnet.
[0025] Comparative Example 1 A method for preparing modified magnetic powder comprises the following steps: S1: After ball-milling and blending ferric oxide and strontium carbonate at a molar ratio of 5.8:1, the blended material is sintered in an air atmosphere at a heating rate of 5°C / min to 1150°C and kept at this temperature for 2 hours to obtain a pre-sintered material; the pre-sintered material is crushed to obtain magnetic powder with a particle size of 1.1 um; S2: Add 10 g of magnetic powder and 25 mL of anhydrous ethanol into a reactor and disperse them evenly. Add 0.2 mL of γ-glycidyloxypropyltrimethoxysilane into the reactor. Control the temperature at 35°C and keep the reaction for 3 hours. Filter and dry to obtain modified magnetic powder.
[0026] Comparative Example 2 A method for preparing modified magnetic powder comprises the following steps: S1: After ball-milling and blending ferric oxide and strontium carbonate at a molar ratio of 5.8:1, the blended material is sintered in an air atmosphere at a heating rate of 5°C / min to 1150°C and kept at this temperature for 2 hours to obtain a pre-sintered material; the pre-sintered material is crushed to obtain magnetic powder with a particle size of 1.1 um; S2: Add 10 mL of tetraethyl orthosilicate and 30 mL of anhydrous ethanol into the reactor and disperse them evenly, then add 3 mL of deionized water, adjust the pH to 5, control the temperature at 45 °C, and keep the reaction for 0.5 h to obtain a modified solution; S3: Add 10g of magnetic powder and 25mL of anhydrous ethanol into a reaction kettle and disperse them evenly. Add 4.8mL of the modified liquid into the reaction kettle, control the temperature at 35°C, keep the reaction warm for 3h, filter and dry to obtain component 1. S4: Disperse 10 g of magnetic powder, 1.8 mL of γ-glycidyloxypropyltrimethoxysilane, 30 mL of anhydrous ethanol, and 30 mL of anhydrous ethanol evenly, filter, and dry to obtain modified magnetic powder.
[0027] Comparative Example 3 A method for preparing a permanent ferrite-based composite bonded magnet comprises the following steps: 10 g of polyphenylene sulfide and 90 g of the modified magnetic powder prepared in Comparative Example 1 were blended and extruded and injection molded at 310° C. to obtain a permanent ferrite-based composite bonded magnet.
[0028] Comparative Example 4 A method for preparing a permanent ferrite-based composite bonded magnet comprises the following steps: 10 g of polyphenylene sulfide and 90 g of the modified magnetic powder prepared in Comparative Example 2 were blended and then extruded and injection molded at 310° C. to obtain a permanent ferrite-based composite bonded magnet.
[0029] Performance Testing (1) Impact strength: tested according to the simply supported beam test in GB / T 1843-2008 "Plastic cantilever beam impact test method", the test results are shown in Table 1; (2) Magnetic properties: The magnets prepared in Examples 4-6 and Comparative Examples 3-4 were measured using an AMT-4 type automatic magnetization characteristic measuring instrument and hysteresis loops were drawn. The remanence, coercive force and maximum magnetic energy product were obtained based on the curves. The test results are shown in Table 1. (3) Flowability: According to ASTM D 123-98, the melt flow rate was tested using a VPXRZ-400C melt flow rate tester under the following conditions: 310°C and 10 kg. The test results are shown in Table 1. Table 1: Statistical table of performance test data of Examples 4-6 and Comparative Examples 3-4
[0030] It can be seen from Table 1 that the bonded magnet prepared in the present application has high fluidity and mechanical properties, and maintains high magnetic properties.
[0031] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a permanent ferrite-based composite bonded magnet, characterized in that: The method comprises the following steps: blending polyphenylene sulfide and modified magnetic powder, and then extruding and injection molding to obtain a permanent ferrite-based composite bonded magnet; The preparation method of the modified magnetic powder comprises the following steps: S1: Add tetraethyl orthosilicate and anhydrous ethanol into a reaction kettle and disperse them evenly, add γ-glycidyloxypropyltrimethoxysilane and disperse them evenly, add deionized water, adjust the pH to 4-6, control the temperature to 40-50°C, keep the temperature for reaction for 0.5-1h, and obtain a modified solution; S2: Add magnetic powder and anhydrous ethanol into a reaction kettle and disperse them evenly, add the modified liquid into the reaction kettle, control the temperature at 30-40°C, keep the reaction warm for 3-6 hours, filter and dry to obtain modified magnetic powder.
2. The method for preparing a permanent ferrite-based composite bonded magnet according to claim 1, characterized in that: The addition ratio of tetraethyl orthosilicate, anhydrous ethanol, γ-glycidyloxypropyltrimethoxysilane and deionized water in S1 is 10mL: 20-40mL: 1-2mL: 1-5mL.
3. The method for preparing a permanent ferrite-based composite bonded magnet according to claim 1, characterized in that: The addition ratio of magnetic powder, anhydrous ethanol and modification liquid in S2 is 10g:20-30mL:3-6mL.
4. The method for preparing a permanent ferrite-based composite bonded magnet according to claim 1, characterized in that: The polyphenylene sulfide accounts for 10-12% of the total weight of the bonded magnet.
5. The method for preparing a permanent ferrite-based composite bonded magnet according to claim 1, characterized in that: The temperature of the extrusion injection molding is 290-320°C.
6. The method for preparing a permanent ferrite-based composite bonded magnet according to claim 1, characterized in that: The method for preparing the magnetic powder comprises the following steps: A1: ball-milling and blending ferric oxide and strontium carbonate, and then pre-calcining to obtain a pre-calcined material; A2: After the pre-sintered material is crushed, magnetic powder is obtained.
7. The method for preparing a permanent ferrite-based composite bonded magnet according to claim 6, characterized in that: The molar ratio of ferric oxide to strontium carbonate is 5.5-5.8:
1.
8. The method for preparing a permanent ferrite-based composite bonded magnet according to claim 6, characterized in that: The specific procedure of pre-sintering is: heating rate 5-10℃ / min, heating to 1100℃-1200℃, keeping warm for 2-4h.
9. A permanent ferrite-based composite bonded magnet, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.